(untitled) (Dubuque, IA, 2008)
This twelfth edition of Taking sides : Clashing views United States history, Volume 1 presents current controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. Each issue is thoughtfully framed with an issue summary, an issue introduction, and a postscript. An instructor's manual with testing material is available for each volume.